(untitled) (Bulletin of criminological association of Ukraine, 2025)
This article examines modern ideas about shaping the typical forensic characteristic of criminal offenses in the economic sphere as a basis for developing effective investigation methods. It highlights the importance of understanding common patterns in how these crimes are committed, including abuse in areas such as goods circulation, finance, privatization, customs procedures, and other sectors of economic activity. The components of the forensic characteristic are identified, including: the method of committing offenses, the circumstances and location of the crime, the trace evidence, the identity of the offender, and the motives and objectives behind the criminal acts. Special focus is given to criminological features that reflect regional differences in economic crime prevalence, the influence of armed conflict on criminal activity, and socio-economic factors that contribute to such acts. The article emphasizes the need to consider modern challenges like digitalization, the transnational nature of crimes, and hybrid criminal forms. It concludes that continuous updates to the forensic characteristic are essential, incorporating empirical data, criminological approaches, and international best practices in combating economic crimes.